Last shot - Hurwitz, Gregg; Hoye, Stephen ([Santa Ana, Calif.] : Books on Tape, 2006)
A seemingly impossible prison escape. A powerful and corrupt company. And a little boy's life hanging in the balance. Three startling plot threads come together as deputy U.S. Marshal Tim Rackley faces the most deadly adversary of his career - a man whose lethal skills, cunning, and single-minded determination make him a mirror image of Rackley himself. Walker Jameson, dishonored Recon Marine, has pulled off an impossible break from California's Terminal Island Penitentiary. After starting a riot, he literally vanishes from his cell, leaving behind only a cup of mouthwash, a strand of dental floss tied to one cell bar, and the body of a sadistic killer. A riveting thriller, a shocking look behind the scenes of one of America's most corrupt corporate sectors, and an exploration of the depths of a mother's love, Last shot is a white-knuckled, complex drama full of razor-sharp action and starling twists and turns, written by one of the finest suspense novelists working today.
Downloadable audio file.
Title from: Title details screen.
Unabridged.
Duration: 16:20:22.
Read by Stephen Hoye.
Requires OverDrive Media Console (file size: 234902 KB).
Keywords: Rackley, Tim (Fictitious character) -- Fiction; Prisoners -- Fiction; Escapes -- Fiction; Prisonniers -- Romans, nouvelles, etc; Evasions -- Romans, nouvelles, etc; Audiobooks; Fiction; Psychological fiction; Suspense fiction